Driving Factors of Carbon Emission Intensity for China's Planting: A Combination of LMDI and PDA - Yang, Fuxia; Fan, Dongshou; Xu, Fei (Frontiers in Climate, 2022)
It is important to explore the driving factors of the carbon emissions intensity (CI) for China’s planting under the dual pressures of adequate food supply and carbon neutrality. Previous studies separately investigate the impact of technical or structural factors on the total carbon emissions of China’s agricultural sector, but few literature assesses the comprehensive effects of the two ones. To the end, this paper incorporates the production-theoretical decomposition analysis(PDA) into the LMDI, and decomposes the changes of CI into seven components, including two technical effects, four structural ones and one regional layout effects. Based on the panel data of the agricultural sector for 31 provinces in China from 2001 to 2018, the contribution rates of the seven components to the changes of China’s planting CI are computed. The results indicate that: China’s planting CI presents a downward trend with an average annual decreasing rate of 11.4% over the whole study period. The improvement of technical efficiency (TEFF) plays a dominant role in the decline of CI for planting with a contribution rate of 83.19%, followed by the output structure (OS) change (27.28%). On the contrary, technical change (TECH) (8.00%) promotes the increase of CI. Further, the effects present a significant regional heterogeneities. Specifically, TEFF contributes the highest share to the decline of CI for producing-sales balance areas (BA), and OS plays the greatest role in the decrease of CI for main grain-sales areas (MCA) during the entire study period. Accordingly, some policy recommendations are put forward on how to reduce the carbon emission intensity of China’s planting.